Implementing cross-border interbank lending in BoC-GEM-FIN - Malik Shukayev; Argyn Toktamyssov (Bank of Canada, 2016)
BIS interbank lending data show that the Great Recession generated large and persistent changes in the international interbank lending positions of various countries. The main objective of this study is to understand the role of changes in international interbank credit flows in transmitting shocks across borders. To accomplish this task, we needed a global structural model with an international interbank market. Our search for a suitable structural model revealed that the Bank of Canada version of the global economy model (BoC-GEM-FIN) comes closest to our needs. BoC-GEM-FIN includes region-specific interbank markets, as well as some international borrowing and lending, but abstracts from the international interbank lending. This paper describes the modifications we made in order to introduce the international interbank market into BoC-GEM-FIN. The modified model is calibrated to match the changes in international interbank lending positions and the decline in the business lending of US banks that took place after the fourth quarter of 2008. Our simulations show that the international interbank market amplifies spillover effects of demand shocks but does not systematically alter the effects of supply shocks, including those for commodities.
Keywords: E27; E37; F47; 330; Economic models; International topics; Business fluctuations and cycles